Leukocyte diversity in resolving and nonresolving mechanisms of cardiac remodeling - Tourki, Bochra (FASEB J, 2017)
In response to myocardial infarction (MI), time-dependent leukocyte infiltration is critical to program the acute inflammatory response. Post-MI leukocyte density, residence time in the infarcted area, and exit from the infarcted injury predict resolving or nonresolving inflammation. Overactive or unresolved inflammation is the primary determinant in heart failure pathology post-MI. Here, our review describes supporting evidence that the acute inflammatory response also guides the generation of healing and regenerative mediators after cardiac damage. Time-dependent leukocyte density and diversity and the magnitude of myocardial injury is responsible for the resolving and nonresolving pathway in myocardial healing. Post MI, the diversity of leukocytes, such as neutrophils, macrophages, and lymphocytes, has been explored that regulate the clearance of deceased cardiomyocytes by using the classic and reparative pathways. Among the innovative factors and intermediates that have been recognized as essential in acute the self-healing and clearance mechanism, we highlight specialized proresolving mediators as the emerging factor for post-MI reparative mechanisms—translational leukocyte modifiers, such as aging, the source of leukocytes, and the milieu around the leukocytes. In the clinical setting, it is possible that leukocyte diversity is more prominent as a result of risk factors, such as obesity, diabetes, and hypertension. Pharmacologic agents are critical modifiers of leukocyte diversity in healing mechanisms that may impair or stimulate the clearance mechanism. Future research is needed, with a focused approach to understand the molecular targets, cellular effectors, and receptors. A clear understanding of resolving and nonresolving inflammation in myocardial healing will help to develop novel targets with major emphasis on the resolution of inflammation in heart failure pathology.—Tourki, B., Halade, G. Leukocyte diversity in resolving and nonresolving mechanisms of cardiac remodeling.